Surgical anatomy of the duodenal papilla. - Estapé, Gonzalo; Boudrandi, Sonia; Veirano, Gustavo; Cardozo, Ricardo; Neirotti, Rubens; Neirotti, Guillermo (Cirugía del Uruguay, 1987)
A macroscopic and topographic study was made of papilla in 123 duodeno-pancreas anatomic pieces and 200 cholangiographies finding that in 68% of cases they are distally located al the mid third of D11, they are conic in 79,5% of cases and flat in the other; the caracteristic folds (cap and frenum) are complete in 78,3% of them. In the irrigation exam there appear three constan! pedicles. Results are discussed and conclusions drawn on main points of anatomo-surgical relevancy